1990
DOI: 10.5014/ajot.44.11.978
|View full text |Cite
|
Sign up to set email alerts
|

Child Abuse as an Antecedent of Multiple Personality Disorder

Abstract: Until recently, few cases of multiple personality disorder were diagnosed in children. Today, the number of cases is increasing at an alarming rate and appears to be most closely associated with repeated sexual and physical abuse. This paper focuses on reports of childhood multiple personality disorder in the literature, the etiology of this disorder, family dynamics, the differences between childhood and adult multiple personality disorder, credibility problems in children, reasons for failure to diagnose mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…Crea ng the life story of the alterna ve personality Intolerable trauma Figure 1. DID as a wide range of defense mechanisms against childhood trauma develop mentally and physically [3,9,14]. An example that confirms this hypothesis is the case a five-year-old Shari who was raped multiple times by a group of teenagers from the neighborhood.…”
Section: Addi On Of An Imaginary a Ributes Combined With The Real Quamentioning
confidence: 99%
See 2 more Smart Citations
“…Crea ng the life story of the alterna ve personality Intolerable trauma Figure 1. DID as a wide range of defense mechanisms against childhood trauma develop mentally and physically [3,9,14]. An example that confirms this hypothesis is the case a five-year-old Shari who was raped multiple times by a group of teenagers from the neighborhood.…”
Section: Addi On Of An Imaginary a Ributes Combined With The Real Quamentioning
confidence: 99%
“…Z zebranych danych wynika, że osobowość mnoga jest prawdopodobnie szerokim wariantem mechanizmów obronnych dziecka przed ekstremalnymi, traumatycznymi zdarzeniami z dzieciństwa, z którymi radzi sobie poprzez wytworzenie alternatywnych osobowości [1][2][3][9][10][11][12]14]. Wskazują na to wszystkie przytoczone modele powstawania DID.…”
Section: Wyniki I Dyskusja -Did Jako Odpowiedź Na Traumę Z Dzieciństwaunclassified
See 1 more Smart Citation
“…Once thought to be rare, about 200 cases were reported in the world literature before 1980 (Bliss, 1980). As awareness of this outcome of child abuse continues to grow, more cases are likely to be diagnosed, therefore occupational therapists have a responsibility to be aware of the symptoms and treatment of this psychiatric disorder (Baldwin, 1990). A recent study in Winnipeg showed that 5% of inpatients in a general psychiatry unit met the criteria for MPD (Ross, Anderson, Fleisher & Norton, 1990).…”
Section: Résumémentioning
confidence: 99%
“…Multiple personality disorder is believed to originate in childhood as a result of severe abuse, especially sexual and physical abuse (Coons, 1986;Wilbur, 1984a). An increasing number of patients with multiple personality disorder are reported to have been childhood and adolescent victims of satanic or sex cult abuse involVing extreme, ritualistic sexual and physical torture (BaldWin, 1990;Snowden, 1989). It appears, however, that in most cases, multiple personality disorder is not uncovered or diagnosed until the patient is between 20 and 40 years of age (Kluft, 1984) The overall ratio of female to male patients with multiple personality disorder has been reported to be between 4: 1 and 7:1.…”
Section: The Original or Presenting Personalitymentioning
confidence: 99%